Implementasi Pendekatan Pembelajaran Mendalam (Deep Learning) dalam Pembelajaran Digital untuk Meningkatkan Kemampuan Literasi Siswa - Herwandi Sape; Lukman Lukman; Habiba Ulfahyana (Cerdas: Jurnal Ilmu Pendidikan Sosial dan Humaniora, 2025)
This study aims to analyze the effect of implementing the Deep Learning approach in digital learning on students’ mathematical literacy skills. The study employed a quantitative approach using a one-group experimental design with a one-group pretest–posttest model. The research subjects consisted of all eighth-grade students of SMA PGRI Tamalate, totaling 30 students. The learning process was conducted in mathematics instruction by applying the Deep Learning approach integrated into digital learning. The research instrument was a mathematical literacy test administered before and after the intervention. Data were analyzed using descriptive and inferential statistics. The prerequisite analysis was conducted through a normality test, while hypothesis testing employed a paired sample t-test. The results indicated an improvement in students’ mathematical literacy skills from a low category in the pretest to a high category in the posttest. The paired sample t-test results revealed a statistically significant difference between pretest and posttest scores, with a significance value of less than 0.05. The N-Gain value was classified as high, indicating that the implementation of the Deep Learning approach in digital learning was effective in improving students’ mathematical literacy skills.